Retinal vessel diameter changes after 6 months of treatment in the Idiopathic Intracranial Hypertension Treatment Trial - Moss, Heather E; Hollar, Rachel A; Fischer, William S; Feldon, Steven E (British journal of ophthalmology, 2020)
Background/AimsPrior studies support an association between increased retinal venule diameter and elevated intracranial pressure (ICP). The purpose of this study was to test the hypothesis that retinal venule diameters decrease in association with long-term therapy for high ICP in subjects with idiopathic intracranial hypertension (IIH).MethodsThis is a retrospective analysis of multicentre randomised controlled trial data. Standardised procedures were used to measure area of optic nerve head elevation (ONHA) and diameters of 4 arterioles and 4 venules 2.7 mm from the optic disc centre on fundus photos collected at baseline and after 6 months of randomised treatment with placebo+diet or acetazolamide+diet in subjects participating in the IIH Treatment Trial (IIHTT) (n=115). Change in arteriole (Da) and venule (Dv) diameters from baseline to 6 months was studied as a function of IIH, haemodynamic and demographic variables.ResultsDv decreased following 6 months of therapy (8.1 µm, 5.9%, p<0.0005) but Da did not change. Dv change was associated with ONHA change (p<0.0005, r=0.47) and this association persisted in multiple variable models.ConclusionsRetinal venule diameter decreased, and arteriole diameter did not change in association with treatment for elevated ICP with a weight loss intervention and placebo or acetazolamide in IIHTT participants. Further study is needed to determine how retinal vessel measurements can be combined with other clinical observations to inform disease management.